2017
DOI: 10.1007/s00520-017-3871-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing a post-treatment survivorship care plan to help breast cancer survivors understand their fertility

Abstract: BCS have concerns and needs related to their fertility potential after initial breast cancer treatment. The evidence-based information offered in our prototype survivorship care plan was acceptable to BCS and has significant potential to address these needs. Additional primary data that identify post-cancer treatment indicators of fertility would advance this effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The unmet gap in reproductive health care is supported by our observation that the majority of YBCS who screened for eligibility had at least one reproductive health issue. A considerable body of research and professional society guidelines on assessing and managing these reproductive health issues has been generated, but lacks broader dissemination [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unmet gap in reproductive health care is supported by our observation that the majority of YBCS who screened for eligibility had at least one reproductive health issue. A considerable body of research and professional society guidelines on assessing and managing these reproductive health issues has been generated, but lacks broader dissemination [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The panel was comprised of 2 YBCS advocates and 6 investigators with clinical and research expertise in reproductive health, primary care, breast oncology, health behavior and randomized trials. To develop the intervention, we conducted systematic reviews and searched professional medical society guidelines for evidence on managing hot flashes and sexual health, addressing contraception needs and predicting fertility potential [23][24][25]. Supplemented by clinical expertise and review of existing webbased resources from professional medical societies and cancer advocacy groups, these evidence-and guideline-based practices were summarized into the SCP-R prototype.…”
Section: Intervention Prototype Development and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…As researchers and clinical providers who work with AYA survivors, we have observed that the occurrence of infertility as well as uncertainty around reproductive risks result in distress, depression, and poorer quality of life in this population. 4,8,127130 Meeting the fertility goals of this population requires not only sound epidemiologic research to estimate risks of traditional and novel cancer therapies on fertility and pregnancy outcomes, but also better dissemination and implementation strategies to improve the delivery of fertility care.…”
Section: Resultsmentioning
confidence: 99%
“…With the recent voluntary deferral of procreation, especially seen in Western societies, many women, at the time of diagnosis, have yet to initiate family or have not yet completed their family wishes. although surrogacy and adoption can be an option, many women voice a preference for biological parenting [8].…”
Section: Introductionmentioning
confidence: 99%